1958
DOI: 10.1136/bmj.2.5088.80
|View full text |Cite
|
Sign up to set email alerts
|

Folic-acid Studies in Megaloblastic Anaemia Due to Primidone

Abstract: Case 8.-This patient was suffering from malignant hypertension. The initial blood urea was 200 mg. per 100 ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1959
1959
1981
1981

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…The megaloblastic anaemia which occurred during phensuximide and phenobarbitone therapy was refractory to cyanocobalamin but responded promptly to folic acid. This finding is in agreement with the hypothesis of Girdwood and Lenman (1956) and Chanarin et al (1958) that megaloblastic anaemia due to anticonvulsant drugs does not result from tissue depletion of folic acid but arises from an interference with folic acid metabolism.…”
Section: Megaloblastic Anaemia During Combined Phensuximide and Phenosupporting
confidence: 93%
“…The megaloblastic anaemia which occurred during phensuximide and phenobarbitone therapy was refractory to cyanocobalamin but responded promptly to folic acid. This finding is in agreement with the hypothesis of Girdwood and Lenman (1956) and Chanarin et al (1958) that megaloblastic anaemia due to anticonvulsant drugs does not result from tissue depletion of folic acid but arises from an interference with folic acid metabolism.…”
Section: Megaloblastic Anaemia During Combined Phensuximide and Phenosupporting
confidence: 93%
“…Although it is well established that megaloblastic haemopoiesis may occur as a complication of anticonvulsant therapy with phenytoin alone (Hawkins & Meynell, 1954), or primidone alone (Chanarin, Elmes & Mollin, 1958) or in combination with other drugs (Kidd & Mollin, 1957;Stokes & Fortune, 1958;Chanarin, Laidlaw, Loughridge & Mollin, 1960) none of the patients in the present study were found to be anaemic (Table 3) Folic acid deficiency in our patients was also assessed by the urinary excretion of FIGLU following histidine loading (Luhby, Cooperman & Teller, 1959). We found that 7 out of 14 patients receiving anticonvulsant drugs, 6 of 15 on phenothiazines, and 1 of 7 treated with tricyclic drugs, excreted amounts of FIGLU that were above the upper limit of the normal range (18 mg/24h).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these cases responded to folic-acid therapy. More recently Chanarin et al (1958) have studied folic acid utilization by measuring the rate of disappearance of this substance from the plasma in a case of megaloblastic anaemia caused by primidone. They showed that the rate of clearance of intravenously injected folic acid and its oral absorption were normal, and concluded that the anaemia was due to interference with the " tissue metabolism" of folic acid.…”
Section: Discussionmentioning
confidence: 99%